2018
DOI: 10.1016/j.ejor.2017.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Optimal workforce assignment to operations of a paced assembly line

Abstract: To cite this version:Alexandre Dolgui, Sergey Kovalev, Mikhail Kovalyov, Sergey Malyutin, Ameur Soukhal. Optimal workforce assignment to operations of a paced assembly line. European Journal of Operational Research, Elsevier, 2018, 264 (1), pp.200-211. 10.1016/j.ejor.2017 Optimal workforce assignment to operations of a paced assembly line AbstractWe study a paced assembly line intended for manufacturing different products. Workers with identical skills perform non-preemptable operations whose assignment to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Academic studies of the workforce planning problems for production lines were initiated by Akagi et al [1] and Wilson [44]. Recent surveys of the results in this field are given by Battaïa and Dolgui [6], Battaïa et al [5], De Bruecker et al [16] and Dolgui et al [17]. Further information can be found in Vairaktarakis et al [42], Polat et al [32], Dalle Mura and Dini [14], Yilmas and Yilmas [47], Zacharia and Nearchou [48] and Ritt et al [34].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Academic studies of the workforce planning problems for production lines were initiated by Akagi et al [1] and Wilson [44]. Recent surveys of the results in this field are given by Battaïa and Dolgui [6], Battaïa et al [5], De Bruecker et al [16] and Dolgui et al [17]. Further information can be found in Vairaktarakis et al [42], Polat et al [32], Dalle Mura and Dini [14], Yilmas and Yilmas [47], Zacharia and Nearchou [48] and Ritt et al [34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…MinMaxSum problem is a subproblem of the industrial problem studied within European project "amePLM" (Battaïa et al [5], Dolgui et al [17]). In the industrial case, two or three automotive engines (two or three part types) are produced in the proportion of 75% and 25% in the case of two engines and 75% and 20% and 5% in the case of three engines on an assembly line comprising of 11 stations.…”
Section: Introductionmentioning
confidence: 99%
“…Problem consists of assigning workers to work station. Study proposed a solution using computer experiment with real and simulated data [19]. Productivity is a key parameter for all manufacturing industries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study of assembly line design, balancing, and scheduling problems is widely reported in the literature (Dolgui et al 2018). Although worker assignment and two-sided assembly line balancing have been thoroughly studied separately, there is limited work reported considering all the characteristics of the considered problem, namely the integrated two-sided assembly line worker assignment and balancing problem with cycle time minimization criterion.…”
Section: Literature Reviewmentioning
confidence: 99%